PAKISTANI WOMEN’S DIETARY AND BEHAVIOURAL PRACTICES IN POSTPARTUM PERIOD - Qamar, Muhammad Aslam; Zareen, Humaira; Malik, Maujid Masood (Pakistan Journal of Physiology, 2016)
Objective: To explore women’s dietary and behavioural practices in postpartum period. Methods: This was a cross sectional study conducted in Department of Gynaecology & Obstetrics FFH Rawalpindi. Five hundred women in their puerperal period coming to FFH responded to the questionnaire and the data were collected. Results: Eighty percent of population had some kind of dietary restrictions during this period and majority (73%) had restriction of cooling diet. Eighty four percent of women were advised to take special diet named ‘Punjeeri’ during purpureum. In behavioural taboos, 72% of women were confined to their houses, 69% were advised to use extra clothing to cover body and overheating of room to avoid cold air currents. Regarding breast-feeding, most of them started this immediately (67%). Majority of them got information and instructions about puerperal practices from their elderly family member (75%). Conclusion: Traditional postpartum behaviours are still very popular in rural area. These are transmitted generation after generation by means of beliefs, customs and taboos. Pak J Physiol 2012;12(2):15–8